Identification of Students Knowledge on Local Games As a Basis to Develop Elementary School Science Textbook - Riyanto Riyanto; Diyah Aryulina; Suwarsono Suwarsono (Universitas Bengkulu, 2019)
The purpose of this study was to identify student knowledge on local games as a basis to develop science elementary school science textbook containing life skills and local games. Descriptive method with questionnaire as an instrument was used to conduct the study on 2160 elementary school students in Bengkulu Province. The results of the study showed that students’ knowledge related to local games was generally categorized as fair. Student knowledge related to knowledge on traditional games was quite various. Based on the study, the local games to be included in the development of elementary school science textbook were reviewed again. Local games known by most students are used as a basis to begin each chapter or subchapter of the textbook, whereas learning sources known by more than 80% students were implemented as chapter themes.